Experienced hearing aid users' perspectives of assessment and communication within audiology: a qualitative study using digital methods. (1st November 2022) - Parmar, Bhavisha J.; Mehta, Kinjal; Vickers, Deborah A.; Bizley, Jennifer K.
Abstract: Objective: To explore experienced hearing aid users' perspectives of audiological assessments and the patient–audiologist communication dynamic during clinical interactions. Design: A qualitative study was implemented incorporating both an online focus group and online semi-structured interviews. Sessions were audio-recorded and transcribed verbatim. Iterative-inductive thematic analysis was carried out to identify themes related to assessment and communication within audiology practice. Study samples: Seven experienced hearing aid users took part in an online focus group and 14 participated in online semi-structured interviews (age range: 22 − 86 years; 9 males, 11 females). Results: Themes related to assessment included the unaided and aided testing procedure and relating tests to real world hearing difficulties. Themes related to communication included the importance of deaf aware communication strategies, explanation of test results and patient centred care in audiology. Conclusion: To ensure hearing aid services meet the needs of the service users, we should explore user perspectives and proactively adapt service delivery. This approach should be ongoing, in response to advances in hearing aid technology. Within audiology, experienced hearing aid users' value (1) comprehensive, relatable hearing assessment, (2) deaf aware patient–audiologist communication, (3) accessible services and (4) a personalised approach to recommend suitable technology and address patient specific aspects of hearing loss.